MANAGERIAL ECONOMICS: ANALYSIS PROBLEMS CASES - Truett Dale; Truett Lila (South-Western Publishing Co, 1998)
THE FIRM AND ITS ENVIROMENT PRODUCTION, COST, AND PROFIT MAXIMIZATION MARKETS AND THE BEHAVIOR OF THE FIRM ANALYSIS OF PROJECT DECISIONS THE FIRM AND THE PUBLIC SECTOR
THE FIRM AND ITS ENVIROMENT PRODUCTION, COST, AND PROFIT MAXIMIZATION MARKETS AND THE BEHAVIOR OF THE FIRM ANALYSIS OF PROJECT DECISIONS THE FIRM AND THE PUBLIC SECTOR